2017
DOI: 10.1038/s41598-017-12954-8
|View full text |Cite
|
Sign up to set email alerts
|

Climates on incidence of childhood type 1 diabetes mellitus in 72 countries

Abstract: We are aimed to systematically assess the worldwide trend in incidence of childhood type 1 diabetes mellitus (CT1DM) from 1965 to 2012 and to discuss whether climate affect incidence of CT1DM. We searched the relevant literatures in detail to judge the effect of different climates on incidence of CT1DM. The climates included Mediterranean, monsoon, oceanic, continental, savanna, and rainforest. According to different climates, we further researched relevant factor such as sunshine durations and latitudes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 113 publications
4
21
1
3
Order By: Relevance
“…Finns, similar Norwegians living in the far north, are unable to produce vitamin D 3 in their skin from sun exposure for more than half a year during the winter and early spring and late fall [ 13 , 92 , 93 ]. This is also supported by the previous report that type 1 diabetes is more common in countries with high latitude and short daytime period [ 94 ].…”
Section: Vitamin D and Immune-related Diseasessupporting
confidence: 90%
“…Finns, similar Norwegians living in the far north, are unable to produce vitamin D 3 in their skin from sun exposure for more than half a year during the winter and early spring and late fall [ 13 , 92 , 93 ]. This is also supported by the previous report that type 1 diabetes is more common in countries with high latitude and short daytime period [ 94 ].…”
Section: Vitamin D and Immune-related Diseasessupporting
confidence: 90%
“…Type 1 diabetes is one of the most prevalent chronic diseases in childhood. Its incidence is rapidly increasing worldwide [1][2][3][4][5]. Type 1 diabetes is caused by a progressive but heterogeneous autoimmune destruction of the beta cells resulting in lack of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, vitamin D deficiency has been increasingly suggested as a risk factor for several autoimmune diseases [74,[107][108][109][110][111], including T1D [112][113][114][115]. Several studies showed that incidence of T1D is directly correlated with latitude and inversely correlated with ultraviolet radiation [116][117][118][119][120]. A number of observational studies showed that subjects with new-onset and established T1D exhibited significantly lower levels of 25(OH)D compared to healthy controls [121][122][123][124][125][126][127][128][129][130].…”
Section: Role Of Vitamin D In Autoimmune Diabetes: T1d and Ladamentioning
confidence: 99%